Ponder2: A Policy System for Autonomous Pervasive Environments - Twidle,K; Lupu,E; Sloman,M; Dulay,N (IEEE, 2009)
Policies form an important part of management and can be an effective means of implementing self-adaptation in pervasive systems. Most policy-based systems focus on large-scale networks and distributed systems. Consequently, they are often fragmented, dependent on infrastructure and lacking ﬂexibility and extensibility. This paper presents Pon- der2, a novel policy system that is suitable for a wide range of environments and applications. The design and implementation of Ponder2 emphasises simplicity, ﬂexibil- ity and extensibility and provides users with the ability to interact easily with the managed system. Ponder2 can interact with other software and hardware components and is being used in environments ranging from single devices, to personal area networks, ad-hoc networks and distributed systems. We also describe PonderTalk, a high-level object orientated language inspired by Smalltalk for conﬁguring and controlling Ponder2 systems.